Pengembangan Kompetensi Sumber Daya Manusia Desa Ekowisata Ciwaluh Melalui Pelatihan Pemandu Wisata - Pratiwi, Brillianing; Arini Noor Izzati; Muhammad Sulaiman; Nunung Supratmi; Lidwina Sri Ardiasih; Jaka Warsihna (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2024)
Ciwaluh Village, Wates Jaya Village, Cigombong District, Bogor Regency, West Java Province has good tourism potential, but the local community is not yet aware of this. Based on the problems mentioned above, community empowerment efforts are needed through community service programs in the Ciwaluh Tourism Village so that it can support the slogan of Bogor district as a tourist city. The goal is to create the development of a tourist village. The methods used are training, mentoring and implementation. Meanwhile, the collaborative partner in implementing Community Service is the Ciwaluh Village Tourism Group, Wates Jaya Village, Cigombong District, Bogor Regency. The aim of Community Service activities in the Ciwaluh Tourism Village is: Increasing Human Resources through Tour Guide Training. The method used is analysis of the competence of human resource managers, analysis of tourism support, analysis of local communities. The result of this activity is an increase in the competency of human resources as tour guides and the active participation of the Ciwaluh tourist village community increases. Participants receive training materials according to their needs as a tourism awareness group that markets Ciwaluh Village with the beauty of the waterfall. Participants can master the training material and the resource person delivers the training material systematically and is easy to understand. Participants considered the training methods and media interesting, and the duration of the training was considered appropriate.